2020
DOI: 10.1161/strokeaha.119.028410
|View full text |Cite
|
Sign up to set email alerts
|

High-Sensitivity Cardiac Troponin T and Cognitive Function in Patients With Ischemic Stroke

Abstract: Background and Purpose— Our study aim was to assess whether high-sensitivity cardiac troponin T (hs-cTnT), a specific biomarker for myocardial injury, is associated with cognitive function in patients after mild-to-moderate first-ever ischemic stroke. Methods— We used data from PROSCIS-B (Prospective Cohort With Incident Stroke Berlin). Cognitive function was assessed by Mini-Mental-State-Examination at baseline, and Telephone Interview for Cognitive St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
26
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 13 publications
4
26
0
1
Order By: Relevance
“…9 The current study provides important insides into the mechanisms of cardiac damage triggered by cerebral ischaemia and contributes to the understanding of the brain-heart syndrome. 10 In line with presented results, elevated high-sensitive cardiac troponin T levels have been frequently observed after stroke. 10,11 In the present study, the authors additionally investigated echocardiographic parameters, such as LVEF and fractional shortening.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…9 The current study provides important insides into the mechanisms of cardiac damage triggered by cerebral ischaemia and contributes to the understanding of the brain-heart syndrome. 10 In line with presented results, elevated high-sensitive cardiac troponin T levels have been frequently observed after stroke. 10,11 In the present study, the authors additionally investigated echocardiographic parameters, such as LVEF and fractional shortening.…”
supporting
confidence: 89%
“…10 In line with presented results, elevated high-sensitive cardiac troponin T levels have been frequently observed after stroke. 10,11 In the present study, the authors additionally investigated echocardiographic parameters, such as LVEF and fractional shortening. The changes of these parameters were observed only in mice with MCAO lasting not 30 min but 60 min.…”
supporting
confidence: 89%
“…Interview for Cognitive Status-modi ed during 3-year follow-up in patients with mild-to-moderate ischemic stroke [20]. The present study, to our knowledge, was the rst longitudinal study to directly characterize the relationship of sST2 and PSCI, extending the connection of heart and brain to the patients with ischemic stroke.…”
Section: Discussionmentioning
confidence: 90%
“…Recently, the PROSCIS-B (Prospective Cohort With Incident Stroke Berlin) study reported that higher hs-cTnT was associated with higher prevalence of cognitive impairment at baseline and lower Telephone Interview for Cognitive Status-modi ed during 3-year follow-up in patients with mild-to-moderate ischemic stroke [20]. The present study, to our knowledge, was the rst longitudinal study to directly characterize the relationship of sST2 and PSCI, extending the connection of heart and brain to the patients with ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation